American sign language : a student text, units 19-27 - Cokely, Dennis; Baker-Shenk, Charlotte Lee (Clerc Books, Gallaudet University Press, 1991)
The third volume in a three-volume guide that introduces beginning students to conversational American Sign Language (ASL).